2012
DOI: 10.1590/s0100-69912012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Atendimento pré-hospitalar à múltiplas vítimas com trauma simulado

Abstract: The triage and transport of victims have been performed satisfactorily. However, more attention should be given to exposure and hypothermia protection of victims, since this item compromised treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
1
14
0
11
Order By: Relevance
“…Concerning the initial care actions for the victim, it was observed that circulatory control, airway opening and cervical control, as well as immobilization were the actions most performed by or in cooperation with the nursing team in MPHC. These results are in line with the study in which it was appointed that airway opening, ventilation and circulatory control were performed in more than 92% of the events ( 19 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the initial care actions for the victim, it was observed that circulatory control, airway opening and cervical control, as well as immobilization were the actions most performed by or in cooperation with the nursing team in MPHC. These results are in line with the study in which it was appointed that airway opening, ventilation and circulatory control were performed in more than 92% of the events ( 19 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Hypothermia is a pre-hospital physiologic parameter predictor of the need for damage control surgery 21 . A study of simulated trauma involving multiple victims, with 40 patients, showed that in 50% of the simulated cases, this aspect was carried out in an inadequate way 22 . The present study corroborates this finding, since the NTL students answered correctly, on average, two of the four questions in both tests, which represents 50% of the questions of item E.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Os prejuízos são de 4,5 milhões em danos materiais, tratamentos médicos, hora-homem de trabalho, indenizações e pensões. 1 No Brasil, os acidentes e a violência configuram um problema de saúde pública de importante magnitude e transcendência, com forte impacto na morbidade e na mortalidade da população.…”
Section: Introductionunclassified